Employee empowerment characteristics and job satisfaction: A review of existing literature and the new avenue of research - Abdul Aziz, Abdullah; Angham Saleem, Obeed Al-Ma'aita (2019)
The role of the employee empowerment strategy in organizational contests has received significant attention in management research. Studies lime investigated whether employee empowerment influencing employees' job satisfaction. Recently, literature provides evidence that companies, under different reasons, focused on the human capital importance in which it directed the organizations and companies paradigms to be changed about the management of people. The main objective of this study is to review the literature that investigated the relationship between employee empowerment and job satisfaction. The literature to date seems to offer inconsistent results, even though studies mostly show significant relationship. This conclusion suggests that the effectiveness of employee empowerment must be improved and future studies should further investigate the role of employee empowerment on mitigating job satisfaction with paying attention to some factors such as the moderating role in this relation. Finally, this review of the literature is hoped to help managers, owners, and researchers to evaluate the employee empowerment role and hence enhancing its monitoring on job satisfaction of employees.